MODULATION OF BONE TISSUE HISTOMORPHOMETRY AND MALONDIALDEHYDE EXPRESSION LEVELS BY VITAMIN C IN RODENTS AFTER PRENATAL NOISE EXPOSURE - Taya Elsa Savista; Viskasari Pintoko Kalanjati; Abdurachman Abdurachman (Universitas Muhammadiyah Sumatera Utara, 2019)
Abstract: Vitamin C is proposed as an antioxidant to combat the oxidative stress of prenatal noise exposure in bone tissue of newborn Wistar rats. Thirty-two Wistar mothers were administered oral vitamin C 150 mg/kg BW/day from D1 of pregnancy until delivery; white noise exposure of 95 dB, 4 hr/day was given from D15 of pregnancy until delivery. Newborn rats were divided into 4 groups equally (n=24): K1 (distilled water), K2 (vitamin C), P1 (distilled water + WN), P2 (vitamin C + WN). The osteoblast and osteoclast mean cell numbers, the osteoid volume, and an oxidative stress expression level marker of malondialdehyde (MDA) were calculated from two adjacent longitudinal slices of newborn rats’ tibiae using Cell Sense and ImageJ softwares (4 μ; 400x of light microscope magnification). Data were analyze using either ANOVA and LSD post-test or Brown-Forsythe and Games Howell post- test; significance level if p<0.05. In P2, the mean number of the osteoblast was significantly higher than in P1 (p<0.001); whilst the osteoclast mean number was significantly lower compared to other groups (p=0.03). In P2, the osteoid volume was significantly higher than in P1 (p=0.021); with lower MDA levels than P1 (p=0.074). From this study, vitamin C could protect the newborn rat bones exposed by prenatal noise as an oxidative stressor.Keywords: vitamin C, prenatal noise, osteogenesis, malondialdehyde